2021
DOI: 10.3390/molecules27010227
|View full text |Cite
|
Sign up to set email alerts
|

Dust-Acoustic Nonlinear Waves in a Nanoparticle Fraction of Ultracold (2K) Multicomponent Dusty Plasma

Abstract: The nonlinear dust-acoustic instability in the condensed submicron fraction of dust particles in the low-pressure glow discharge at ultra-low temperatures is experimentally and theoretically investigated. The main discharge parameters are estimated on the basisof the dust-acoustic wave analysis. In particular, the temperature and density of ions, as well as the Debye radius, are determined. It is shown that the ion temperature exceeds the temperature of the neutral gas. The drift characteristics of all plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…It should be noted that in some cases, DAWs also occurred upon changing the gas pressure. DAWs were observed in various gases at room and cryogenic temperatures [50][51][52], in complex plasma of a non-self-sustained discharge [53], and in a long structure of microparticles confined in the linear Paul trap in air under normal condition [54,55]. Authors of work [56] revealed that, similarly to the discharge plasma, the quadrupole dynamic trap could confine a limited number of charged microparticles.…”
Section: Dynamic State Of Complex Plasmamentioning
confidence: 99%
“…It should be noted that in some cases, DAWs also occurred upon changing the gas pressure. DAWs were observed in various gases at room and cryogenic temperatures [50][51][52], in complex plasma of a non-self-sustained discharge [53], and in a long structure of microparticles confined in the linear Paul trap in air under normal condition [54,55]. Authors of work [56] revealed that, similarly to the discharge plasma, the quadrupole dynamic trap could confine a limited number of charged microparticles.…”
Section: Dynamic State Of Complex Plasmamentioning
confidence: 99%